Diseño de una metodología para el seguimiento de la estabilidad mecánica durante la perforación de un pozo en el Campo Castilla (2018)
Many wells have been drilled in the Castilla Field, located in the Llanos Basin. Stability problems account for a considerable amount of non productive time while drilling. The purpose was to propose a methodology to monitor well-bore mechanical stability while drilling using indirect variables. Some multivariate statistical techniques were applied to the available information of eight wells to identify risk zones. The indirect parameters statistically related to the instability were proposed to be monitored while drilling to reduce the non productive time. Four zones were identified as the most problematic. A characterization was made to the drilling fluid parameters that affect the most the daily costs, selected as the response variable.